Analisis Peran Stakeholders dalam Penertiban Terminal Bayangan di Kota Padang, Studi Kasus: Terminal Bayangan di Depan UNP - Ramadani, Zahara; Putri, Sinta Westika (Lembaga Yasin AlSys, 2025)
The enforcement of informal or “shadow” terminal regulation represents a strategic effort to improve transportation order and safety in Padang City, particularly in the area in front of Universitas Negeri Padang (UNP). Although such terminals offer easier access for passengers and bus drivers, they also contribute to traffic congestion and reduced compliance with transportation regulations. This study aims to analyze the roles of stakeholders in the regulation of shadow terminals in front of UNP, identify supporting and inhibiting factors in policy implementation, and evaluate the effectiveness of inter-stakeholder collaboration. A qualitative descriptive method with a case study approach was employed, involving in-depth interviews with the Padang City Transportation Agency, Civil Service Police Unit (Satpol PP), Padang Utara Police Sector, bus company (PO) managers, bus drivers, and service users. The findings reveal that stakeholder roles fall into five categories: policy creator, coordinator, facilitator, implementer, and accelerator. The roles of implementers and coordinators are the most dominant, carried out through field inspections, ticketing, and supervision, while facilitators and accelerators contribute through internal coordination and feedback from service users. Inhibiting factors include low driver compliance, limited accessibility to official terminals, and insufficient infrastructure. Supporting factors include inter-stakeholder synergy, cross-agency coordination, and growing awareness among service users of the importance of transportation order. These findings offer valuable insights into stakeholder dynamics and provide strategic recommendations to enhance the effectiveness of shadow terminal enforcement in Padang City.